High-wear-resistance anti-corrosion ceramic automobile brake disc and preparation method thereof
By adopting a gradient integrated coating design with gradient composition on the ceramic coating and aluminum-based composite substrate, combined with plasma spraying technology, the stress problem caused by the difference between the ceramic coating and the substrate is solved, and a high wear-resistant and rust-resistant ceramic automobile brake disc is achieved.
Patent Information
- Application Number
- CN202510123422.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-26
AI Technical Summary
During use, the existing ceramic coatings have great differences between the thermal expansion coefficient and hardness and the substrate, resulting in excessive stress in the coating and failure.
The gradient integrated coating design with gradient morphology is used to combine the ceramic coating with an aluminum-based composite substrate and made through plasma spraying technology to form a uniform and dense ceramic coating.
The thermal insulation and wear resistance of ceramic coatings are achieved, while ensuring good bonding ability with the substrate, improving the hardness and wear resistance of the coatings, and extending service life.
Smart Images

Figure CN119843201A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction, and in particular to a highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof. Background Art
[0002] The technical basis of metal ceramic coating comes from the National 863 Major Project and has been successfully applied in major national technical equipment (exhaust gas power generation equipment of a refinery of Sinopec in Lanzhou). The coating service life and performance of its generator smoke fan blades are better than similar coatings in the United States. This type of coating can also be used for water-cooled wall tubes, reheat tubes, superheater tubes and economizer tubes (commonly known as boiler four tubes) of industrial boilers in thermal power plants and papermaking, chemical industry, etc., as well as high-temperature resistant shaft sleeves, high-temperature valve sealing surfaces, engine valve cores, etc. in the fields of metallurgy and heavy chemical industry.
[0003] For example, the Chinese patent with application number CN202210785551.8 discloses a composite structure lightweight ceramic brake disc and its preparation method. The composite structure lightweight ceramic brake disc composed of a friction layer with high friction and wear performance and a structural layer with high strength and heat storage has excellent comprehensive performance and realizes the integration of product structural characteristics and functional characteristics. The friction layer has high density, low porosity, strong environmental adaptability, excellent friction and wear performance, especially wet braking and high kinetic energy braking, small friction performance attenuation, good braking performance stability, and high thermal safety.
[0004] For example, the Chinese patent application number CN202310403339.5 discloses a method for preparing a carbon-ceramic brake disc. The carbon-ceramic brake disc uses 4-phenyl-3-thiosemicarbazide-modified chopped carbon fibers as a mixed slurry component, and an injection molding process is used to prepare a brake disc blank. The carbon-ceramic brake disc obtained by carbonization, rough processing, and ceramicization has good bulk density, mechanical properties, thermal conductivity, and friction resistance. The present invention also uses 5-tert-butyl-2-methoxyaniline to modify the resin, which is then used in the preparation of the carbon-ceramic brake disc, so that the carbon-ceramic brake disc has better bulk density, mechanical properties, thermal conductivity, and friction resistance.
[0005] For example, the Chinese patent application number CN202310572574.5 discloses a composite process for carbon-ceramic brake discs with uniform ceramic composite carbon fibers. The present invention adopts FeSi75-modified C / C-SiC composite material to prepare carbon-ceramic brake discs with uniform ceramic composite carbon fibers; 2-decyltetradecane-p-mercaptoterephthalate is reacted with vinyl ferrocene, propenyl silsesquioxane, and sodium tert-butoxide to obtain a carbon fiber treating agent; the bundling and smoothness of the fiber bundles of the carbon fiber precursor are improved, and the infiltration effect of the C / C porous composite material and the FeSi75 alloy powder is improved, thereby improving the bending strength and fracture toughness of the carbon-ceramic brake disc.
[0006] When using the above technology, it was found that the following technical problems exist in the prior art: the material of the commonly used thermal barrier coating is usually a ceramic coating. By controlling the process, a high-hardness coating can be prepared, and the coating has excellent wear resistance. Therefore, it is possible to consider designing a ceramic coating of sufficient thickness, which can not only meet the heat insulation function, but also achieve super wear resistance of the coating. However, the thermal expansion coefficient, hardness and other physical properties of a single ceramic coating of sufficient thickness are quite different from those of the substrate, resulting in excessive internal stress in the coating and failure during its use. For this reason, we design a highly wear-resistant and rust-resistant ceramic automotive brake disc and a preparation method thereof, which are used to provide another technical solution to the above technical problems. Summary of the invention
[0007] Based on this, it is necessary to provide a highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof to address the above-mentioned technical problems. The ceramic coating and the aluminum-based composite substrate are designed as a gradient integrated coating with a gradual composition change. In this way, the thermal insulation and wear resistance of the ceramic coating can be achieved, and its good bonding ability with the substrate can be ensured, and the advantages of the metal bonding phase and the hard ceramic phase in the coating can be fully utilized.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions: A highly wear-resistant and rust-resistant ceramic automobile brake disc and a preparation method thereof, wherein the highly wear-resistant and rust-resistant ceramic automobile brake disc is made of an aluminum-based composite substrate, a bonding metal and a ceramic by plasma spraying technology, and then combined with a gradient coating structure to obtain a highly wear-resistant and rust-resistant ceramic automobile brake disc; The preparation method of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc is as follows: S1, preparing an aluminum-based composite substrate, wherein the aluminum-based composite substrate comprises 6% to 8% zinc, 1.5% to 2% copper, 2% to 6% magnesium, and the balance is aluminum, wherein the aluminum-based composite substrate blank is formed by mixing the above materials and smelting at high temperature, and the aluminum-based composite substrate blank is formed by grinding and sandblasting the aluminum-based composite substrate blank; The temperature of the high temperature smelting is 900-1100°C; S2, placing the aluminum-based composite substrate into an inert gas chamber of an ion sprayer, preheating the plasma spray gun to between 80 and 150° C., and during the spraying process, the temperature of the aluminum-based composite substrate needs to be controlled at 200° C.; S3, the ceramic spray powder includes 12% to 18% aluminum oxide, 5% to 8% titanium oxide, 30% to 40% zirconium oxide, and the balance is chromium trioxide. The ceramic spray powder is formed by uniformly mixing the above materials. Under the action of high-pressure gas, the molten or semi-molten ceramic spray powder is sprayed at high speed onto the surface of the aluminum-based composite substrate, and the ceramic spray powder is stacked together in a wave-like manner on the surface of the aluminum-based composite substrate to form a gradient coating structure, thereby forming a metal bonding layer; S4, when the ceramic spray powder particle flow hits the metal bonding layer, it will collide, deform, solidify and accumulate, thus forming a uniform, dense ceramic coating with high hardness and high wear resistance.
[0009] As a preferred embodiment of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc and its preparation method provided by the present invention, the steps of making the aluminum-based composite substrate in S1 are as follows: making a core mold, determining the shape and size of the brake disc by the core mold, pouring the composite aluminum water, pouring the composite aluminum water into the prepared core mold, and completing the production of the brake disc aluminum-based composite substrate blank after the composite aluminum water is cooled.
[0010] As a preferred embodiment of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc and the preparation method thereof provided by the present invention, the operating power of the S2 plasma spray gun is 20~35kW, and the power of the HEPJet high-performance supersonic spraying is 45~65kW.
[0011] As a preferred embodiment of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc and the preparation method thereof provided by the present invention, the spraying angle of the plasma spray gun in S2 is usually 60° to 80°.
[0012] As a preferred embodiment of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc and the preparation method thereof provided by the present invention, the ceramic content of the metal bonding layer formed in S3 is higher than that of the aluminum alloy.
[0013] As a preferred embodiment of the highly wear-resistant and rust-resistant ceramic automobile brake disc and its preparation method provided by the present invention, the ceramic spray powder material sprayed in S3 and the aluminum-based composite substrate will have a certain degree of mutual solubility, thereby enhancing the bonding strength between the coating and the substrate. The coating will undergo a transition process from liquid to solid, and finally tightly bonded to the metal substrate to form a bonding metal layer with the desired properties.
[0014] As a preferred embodiment of the highly wear-resistant and rust-resistant ceramic automobile brake disc and the preparation method thereof provided by the present invention, the thickness of the ceramic coating formed in S4 is 2 mm.
[0015] As a preferred embodiment of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc and the preparation method thereof provided by the present invention, the microhardness of the ceramic coating in S4 is greater than HV1000.
[0016] It can be seen without a doubt that the above-mentioned technical solution of the present application can definitely solve the technical problem to be solved by the present application.
[0017] At the same time, through the above technical solutions, the present invention has at least the following beneficial effects: The present invention provides a highly wear-resistant and rust-resistant ceramic automobile brake disc and a preparation method thereof. The ceramic coating and the aluminum-based composite substrate are designed to be a gradient integrated coating with a gradual change in composition. In this way, the thermal insulation and wear resistance of the ceramic coating can be achieved, and its good bonding ability with the substrate can be ensured, and the advantages of the metal bonding phase and the hard ceramic phase in the ceramic coating can be fully utilized. The ceramic coating has a strong bonding force with the aluminum-based composite substrate, and the adhesion is greatly improved. At the same time, the gradient integrated coating with a gradual change in composition forms a uniform and dense ceramic coating on the surface of the aluminum-based composite substrate, and the ceramic coating has high hardness and strong wear resistance.
[0018] The present invention provides a highly wear-resistant and rust-resistant ceramic automobile brake disc and a preparation method thereof. By using a production method of plasma spraying technology, the heat of processing an aluminum-based composite substrate during coating is reduced, and the risk of deformation of the aluminum-based composite substrate during processing is reduced. In addition, since the parts are not electrified during the spraying process, the aluminum-based composite substrate is not easily damaged. While improving the hardness and wear resistance of the brake disc, the yield rate of the produced brake disc is improved.
[0019] The present invention provides a highly wear-resistant and rust-resistant ceramic automobile brake disc and a preparation method thereof. The brake disc substrate is made of an aluminum alloy and is light in weight. The lighter brake disc can reduce the rotational inertia of the wheel, reduce the energy consumption of the vehicle, and has good heat dissipation performance. The aluminum alloy has excellent thermal conductivity and can effectively dissipate heat. During the braking process, the brake disc will generate a large amount of heat due to friction, and the aluminum alloy brake disc can quickly dissipate the heat to prevent performance degradation caused by high temperature, which ensures the stable operation of the brake system and extends the service life of the brake disc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0021] Figure 1 This is a design idea diagram of the ceramic coating of the present invention; DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0023] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings.
[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features and technical solutions in the embodiments may be combined with each other.
[0025] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0026] Please refer to Figure 1 , a highly wear-resistant and rust-resistant ceramic automobile brake disc and a preparation method thereof, wherein the highly wear-resistant and rust-resistant ceramic automobile brake disc is made of an aluminum-based composite substrate, a bonding metal and a ceramic, through a plasma spraying technology, and then combined with a gradient coating structure to obtain a highly wear-resistant and rust-resistant ceramic automobile brake disc; The preparation method of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc is as follows: Embodiment 1, S1, preparing an aluminum-based composite substrate, wherein the aluminum-based composite substrate comprises 6%-8% zinc, 1.5%-2% copper, 2%-6% magnesium, and the balance is aluminum, wherein the aluminum-based composite substrate blank is formed by mixing the above materials and smelting at high temperature, and the aluminum-based composite substrate blank is formed by grinding and sandblasting the aluminum-based composite substrate blank; The temperature of the high temperature smelting is 900-1100°C; The steps for making the aluminum-based composite substrate in S1 are as follows: making a core mold, feeding the above materials into a high-temperature furnace in sequence, controlling the temperature to 1000° C. under the protection of nitrogen gas, and performing high-temperature smelting for 5 minutes to obtain aluminum-based composite aluminum liquid.
[0027] According to the design drawings and requirements of the brake disc, a precise core mold is made. The shape and size of the brake disc are determined by the core mold, and the composite aluminum water is poured into the prepared core mold. During the pouring process, it is necessary to ensure that the aluminum alloy melt evenly fills the core mold and avoids the generation of bubbles and inclusions to ensure the quality and performance of the brake disc. After pouring, it is cooled by air quenching. The cooling speed and temperature need to be controlled during the cooling and solidification process to avoid thermal stress and cracks. After the composite aluminum water is cooled, the production of the brake disc aluminum-based composite substrate blank is completed.
[0028] In the process of making aluminum-based composite substrates, arc keys and arc grooves need to be reserved on them. Through the design of structures such as arc keys and arc grooves, the ceramic spray powder and the aluminum-based composite substrate can achieve a metallurgical bonding effect and form an alloy transition layer. This transition layer can effectively alleviate the difference in physical properties between different materials, enhance the bonding force, and improve the overall performance and stability of the brake disc. The brake disc substrate is made of aluminum alloy. The density of aluminum alloy is much lower than that of traditional cast iron materials. Therefore, the brake disc made of aluminum alloy is lighter, which effectively reduces the curb weight of the car, thereby improving fuel economy and vehicle handling performance. Lighter brake discs can also reduce the rotational inertia of the wheels, reduce the energy consumption of the vehicle, and have good heat dissipation performance. Aluminum alloy has excellent thermal conductivity and can effectively dissipate heat. During the braking process, the brake disc will generate a lot of heat due to friction, and the aluminum alloy brake disc can quickly dissipate the heat to prevent performance degradation caused by high temperature, which ensures the stable operation of the braking system and extends the service life of the brake disc. It also has excellent corrosion resistance. Aluminum alloy has excellent corrosion resistance and can maintain stable performance in harsh environments. Therefore, the brake disc with aluminum alloy as the substrate has a longer service life and can reduce performance degradation and replacement frequency caused by corrosion.
[0029] Embodiment 2, S2, in order to protect the particle beam during spraying, when coating the aluminum-based composite substrate, the aluminum-based composite substrate is first placed in the inert gas chamber of the ion sprayer, and the plasma spray gun is preheated between 80 and 150°C. During the spraying process, the temperature of the aluminum-based composite substrate needs to be controlled at 200°C. The aluminum-based composite substrate is heated to a certain temperature, which helps to improve the bonding strength between the coating and the substrate. Preheating can reduce the thermal stress between the substrate and the coating during the spraying process, thereby avoiding cracking or falling off of the coating.
[0030] In order to improve the thermal efficiency of the spray gun, the power of the S2 plasma spray gun is 20~35kW, while the power of the HEPJet high-performance supersonic spray is 45~65kW.
[0031] In order to improve the quality of spraying, the spraying angle of the S2 plasma spray gun is usually 60° to 80°. When the spraying angle is too small, the fine powder particles of the ceramic spray powder adhere to the spraying surface, hindering the continued spraying of the ceramic spray powder particles, and forming a "silo" behind it, thereby forming a porous coating with irregular voids. Such voids not only weaken the strength of the coating, but also accumulate fine substances containing high oxides from the jet flow, changing the chemical composition of the coating.
[0032] When the spraying angle is less than 45°, a "shielding effect" of the spraying will occur, affecting the interlayer adhesion of the coating and reducing the bonding strength between the coating and the substrate.
[0033] During operation, after the aluminum-based composite substrate is placed in the inert gas chamber of the plasma processing equipment, the plasma gun muzzle is moved to a distance of 80-150mm from the aluminum-based composite substrate to prevent the ceramic spraying powder from being heated for a short time and insufficiently deformed due to impact due to the spraying distance being too close, and the coating quality being affected. The rapid increase in the influence of the plasma flame flow and temperature will show severe oxidation, resulting in coating shedding. The spraying distance is prevented from being too far, and the powder heated to a molten state will be cooled when it contacts the parts, and the flight speed will be reduced, affecting the coating quality and efficiency. Then, the plasma spray gun moved to a suitable distance is adjusted to a suitable angle, and the plasma spraying equipment is started to spray the aluminum-based composite substrate. The powder feeding process is set to 15-20 grams / minute to form a bonding metal layer on the aluminum-based composite substrate.
[0034] By using the production method of plasma spraying technology, the heat generated by the aluminum-based composite substrate during coating is reduced, and the risk of deformation of the aluminum-based composite substrate during processing is reduced. In addition, since the parts are not electrified during the spraying process, it is not easy to damage the aluminum-based composite substrate. While improving the hardness and wear resistance of the brake disc, the yield rate of the brake disc production is improved. In the plasma spraying process, the particle speed and temperature are high, which makes the porosity of the coating low and the bonding strength with the substrate high, making it less likely for the coating to peel off, crack, and other problems.
[0035] Embodiment three, S3, before spraying, select composite powder with a particle size of generally -140 to +325 mesh, and mix the powders meeting the purpose in the following proportions: ceramic spray powder includes 12% to 18% aluminum oxide, 5% to 8% titanium oxide, 30% to 40% zirconium oxide, and the remainder is chromium trioxide powder material. The ceramic spray powder is formed by uniformly mixing the above materials. Then, plasma (i.e., excited and ionized gas) is used to activate the ceramic spray powder material. The plasma heats the spray material to a molten or semi-molten state through high-temperature and high-speed gas ions and electrons. The molten or semi-molten ceramic spray powder is sprayed at a high speed onto the surface of the aluminum-based composite substrate under the action of high-pressure gas, and is stacked together in a wave-like manner on the surface of the aluminum-based composite substrate to form a gradient coating structure, a metal bonding layer, and an increased density of the coating.
[0036] The ceramic content of the metal bonding layer formed in the S3 is higher than that of the aluminum alloy. The ceramic material has excellent wear resistance, high temperature resistance and a stable friction coefficient. These characteristics make the ceramic brake pad perform better during braking. When the ceramic content in the metal bonding layer is higher than that of the aluminum alloy, the hardness and wear resistance of the brake disc can be significantly improved, and the service life of the brake disc can be extended. In addition, the high temperature stability of the ceramic material helps to reduce the thermal decay phenomenon during braking and maintain a stable braking effect.
[0037] The ceramic spray powder material sprayed in S3 will melt to a certain extent with the aluminum-based composite substrate, thereby enhancing the bonding strength between the coating and the substrate. The coating will undergo a transformation process from liquid to solid, and finally tightly bond with the metal substrate to form a bonding metal layer with the desired properties.
[0038] During operation, 12% to 18% alumina, 5% to 8% titanium oxide, 30% to 40% zirconium oxide and the remainder chromium trioxide which meet the mesh size are put into a mixer and the time is set for thirty minutes to obtain ceramic spray powder. In the process of forming the gradient coating, the composition of the spray material is adjusted. When the ceramic spray powder material is sprayed on the surface of the aluminum-based composite substrate through a plasma spray gun, the aluminum oxide, titanium oxide, zirconium oxide and chromium trioxide in the ceramic spray powder material and the zinc, copper, magnesium and aluminum in the aluminum-based composite substrate are coated with the gradient coating. The organizational structure of the coating reflects that in the ceramic gradient coating, as the coating thickness increases, the content of the ceramic phase component gradually increases, while the content of the metal phase component decreases accordingly. This gradient distribution makes there is no obvious interface between the metal phase and the ceramic phase coating, thereby well solving the problem of mismatched performance between the two, weakening or eliminating the stress in the coating to the greatest extent, and improving the bonding strength between the coating and the substrate.
[0039] The spraying parameters (such as spraying current, spraying distance, powder feeding rate, etc.) as well as the number of spray layers and the composition changes between each layer can achieve a smooth transition from one material to another, thereby forming a coating with the desired performance gradient. This gradient coating can significantly improve the wear resistance, corrosion resistance, heat resistance and other properties of the brake disc and extend its service life.
[0040] By designing the ceramic coating and the aluminum-based composite substrate as a gradient integrated coating with a gradual composition, the thermal insulation and wear resistance of the ceramic coating can be achieved, and its good bonding ability with the substrate can be guaranteed. The advantages of the metal bonding phase and the hard ceramic phase in the ceramic coating can be fully utilized. The ceramic coating has a strong bonding force with the aluminum-based composite substrate and the adhesion is greatly improved. At the same time, the gradient integrated coating with a gradual composition forms a uniform and dense ceramic coating on the surface of the aluminum-based composite substrate. The ceramic coating has high hardness and strong wear resistance.
[0041] Embodiment 4, S4, in order to facilitate the formation of a ceramic coating with uniform thickness outside the bonding metal layer, when the ceramic spray powder particle flow hits the metal bonding layer, collision, deformation, solidification and accumulation will occur, thereby forming a uniform, dense ceramic coating with high hardness and high wear resistance.
[0042] In order to give full play to the advantages of the metal bonding phase and the hard ceramic phase in the coating, the thickness of the ceramic coating formed in S4 is 2 mm.
[0043] During operation, after a ceramic coating with a thickness of 2 mm is formed outside the bonding metal layer, the preparation of a highly wear-resistant and corrosion-resistant ceramic automobile brake disc is completed.
[0044] The microhardness of the ceramic coating in S4 is greater than HV1000, and the coating has excellent wear resistance. Therefore, it is possible to consider designing a ceramic coating of sufficient thickness to satisfy the heat insulation effect and realize the super wear resistance of the coating.
[0045] The invention provides a method for preparing a highly wear-resistant and rust-resistant ceramic automobile brake disc as follows: a worker sequentially feeds a mixed metal of 6%-8% zinc, 1.5%-2% copper, 2%-6% magnesium, and the remainder aluminum into a high-temperature furnace, and sintering at high temperature for 5 minutes under the protection of nitrogen gas at a temperature of 1000°C to obtain aluminum-based composite aluminum liquid. In the process of preparing the aluminum-based composite substrate, arc keys and arc grooves need to be reserved on the aluminum-based composite substrate. By designing structures such as arc keys and arc grooves, the ceramic spray powder and the aluminum-based composite substrate are To achieve the metallurgical bonding effect between the materials, before spraying, a composite powder with a particle size of generally -140 to +325 mesh is selected, and the powders that meet the purpose are mixed in the following proportions: the ceramic spraying powder includes 12% to 18% aluminum oxide, 5% to 8% titanium oxide, 30% to 40% zirconium oxide, and the balance is chromium trioxide. The ceramic spraying powder is uniformly mixed with the above materials. After the mixing is completed, the aluminum-based composite substrate is placed in the inert gas chamber of the ion spray machine, and the plasma spray gun is preheated by The temperature of the plasma spray gun in S2 is between 80 and 150 ° C. In order to improve the quality of spraying, the spraying angle of the plasma spray gun in S2 is usually 60 ° to 80 °. The plasma gun muzzle is moved to a length of 80-150 mm from the aluminum-based composite substrate, and the powder feeding process is set to 15-20 g / min, and then the aluminum-based composite substrate is sprayed. When the ceramic spray powder material is sprayed on the surface of the aluminum-based composite substrate by the plasma spray gun, the aluminum oxide, titanium oxide, zirconium oxide and chromium oxide in the ceramic spray powder material react with the zinc, copper, magnesium and aluminum in the aluminum-based composite substrate to form a coating gradient coating. In the ceramic coating gradient coating, as the coating thickness increases, the content of the ceramic phase component gradually increases, while the content of the metal phase component decreases accordingly. When the ceramic spray powder particle flow hits the metal bonding layer, collision, deformation, solidification and accumulation will occur, thereby forming a uniform, dense ceramic coating with high hardness and high wear resistance. When a ceramic coating with a thickness of 2 mm is formed outside the bonding metal layer, the preparation of a highly wear-resistant and rust-resistant ceramic automotive brake disc is completed.
[0046] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the present invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof, characterized in that: The highly wear-resistant and rust-resistant ceramic automobile brake disc is made of an aluminum-based composite substrate, a bonding metal and a ceramic, and is made by plasma spraying technology, and then combined with the organizational structure of a gradient coating to obtain a highly wear-resistant and rust-resistant ceramic automobile brake disc; The preparation method of the highly wear-resistant and corrosion-resistant ceramic automobile brake disc is as follows: S1, preparing an aluminum-based composite substrate, wherein the aluminum-based composite substrate comprises 6% to 8% zinc, 1.5% to 2% copper, 2% to 6% magnesium, and the balance is aluminum, wherein the aluminum-based composite substrate blank is formed by mixing the above materials and smelting at high temperature, and the aluminum-based composite substrate blank is formed by grinding and sandblasting the aluminum-based composite substrate blank; The temperature of the high temperature smelting is 900-1100°C; S2, placing the aluminum-based composite substrate into an inert gas chamber of an ion sprayer, preheating the plasma spray gun to between 80 and 150° C., and during the spraying process, the temperature of the aluminum-based composite substrate needs to be controlled at 200° C.; S3, the ceramic spray powder includes 12% to 18% aluminum oxide, 5% to 8% titanium oxide, 30% to 40% zirconium oxide, and the balance is chromium trioxide. The ceramic spray powder is formed by uniformly mixing the above materials. Under the action of high-pressure gas, the molten or semi-molten ceramic spray powder is sprayed at high speed onto the surface of the aluminum-based composite substrate, and the ceramic spray powder is stacked together in a wave-like manner on the surface of the aluminum-based composite substrate to form a gradient coating structure, thereby forming a metal bonding layer; S4, when the ceramic spray powder particle flow hits the metal bonding layer, it will collide, deform, solidify and accumulate, thus forming a uniform, dense ceramic coating with high hardness and high wear resistance.
2. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The steps for making the aluminum-based composite substrate in S1 are as follows: making a core mold, determining the shape and size of the brake disc through the core mold, pouring the composite aluminum liquid, pouring the composite aluminum liquid into the made core mold, and completing the production of the brake disc aluminum-based composite substrate blank after the composite aluminum liquid is cooled.
3. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The power of the S2 plasma spray gun is 20~35kW, while the power of the HEPJet high-performance supersonic spray is 45~65kW.
4. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The spraying angle of the S2 plasma spray gun is usually 60° to 80°.
5. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The ceramic content forming the metal bonding layer in the S3 is higher than that of the aluminum alloy.
6. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The ceramic spray powder material sprayed in S3 will melt to a certain extent with the aluminum-based composite substrate, thereby enhancing the bonding strength between the coating and the substrate. The coating will undergo a transformation process from liquid to solid, and finally tightly bond with the metal substrate to form a bonding metal layer with the desired properties.
7. A highly wear-resistant and corrosion-resistant ceramic automobile brake disc and a preparation method thereof according to claim 1, characterized in that: The thickness of the ceramic coating formed in S4 is 2 mm.
8. The highly wear-resistant and corrosion-resistant ceramic automobile brake disc and the preparation method thereof according to claim 1, characterized in that: The microhardness of the ceramic coating in S4 is > HV1000.
Citation Information
Patent Citations
Composite-structure lightweight ceramic brake disc and preparation method thereof
CN115385711A
Preparation method of carbon-ceramic brake disc
CN116136067A
Ceramic-carbon fiber composite process for carbon-ceramic brake discs
CN116283355B
Automobile brake disc and manufacturing method thereof
CN105041921A
Method for preparing low-weight aluminum-based brake disc
CN106670473A
Cited By
Light-weight brake disc with porous matrix-ceramic composite coating and preparation process of light-weight brake disc
CN120626654A
Lightweight brake disc of porous matrix-ceramic composite coating and its preparation process
CN120626654B